2019
DOI: 10.1007/s11538-019-00622-z
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Turgor-Induced Stress Patterns in Multilayered Plant Tissues

Abstract: The intertwining between mechanics and developmental biology is extensively studied at the shoot apical meristem of land plants. Indeed, plants morphogenesis heavily relies on mechanics; tissue deformations are fueled by turgor-induced forces, and cell mechanosensitivity plays a major regulatory role in this dynamics. Since measurements of forces in growing meristems are still out of reach, our current knowledge relies mainly on theoretical and numerical models. So far, these modeling efforts have 1 been mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(60 reference statements)
2
4
0
Order By: Relevance
“…Considering known estimates of the thickness of the Arabidopsis SAM outer cell wall, the authors estimated a stiffness ratio of outer to inner walls to be in the range of 3–10:1. Given these ratios, simulations demonstrate that the periclinal stress patterns (i.e., parallel to the tissue surface) in the outer walls of multilayered SAM models resemble those produced by shell models, thus validating earlier approaches ( Ali et al, 2019 ). A second important conclusion from this work is that maximal stress patterns in the anticlinal walls (i.e., perpendicular to the tissue surface) of both the epidermis and underlying cell layers are predominantly oriented anticlinally ( Ali et al, 2019 ), again matching observed microtubule and cellulose orientations ( Sakaguchi et al, 1988 ; Figure 1B ).…”
Section: A Mechanical Stress Cellulose Fibril Feedback Loop Patterns Plant Morphogenesissupporting
confidence: 77%
See 2 more Smart Citations
“…Considering known estimates of the thickness of the Arabidopsis SAM outer cell wall, the authors estimated a stiffness ratio of outer to inner walls to be in the range of 3–10:1. Given these ratios, simulations demonstrate that the periclinal stress patterns (i.e., parallel to the tissue surface) in the outer walls of multilayered SAM models resemble those produced by shell models, thus validating earlier approaches ( Ali et al, 2019 ). A second important conclusion from this work is that maximal stress patterns in the anticlinal walls (i.e., perpendicular to the tissue surface) of both the epidermis and underlying cell layers are predominantly oriented anticlinally ( Ali et al, 2019 ), again matching observed microtubule and cellulose orientations ( Sakaguchi et al, 1988 ; Figure 1B ).…”
Section: A Mechanical Stress Cellulose Fibril Feedback Loop Patterns Plant Morphogenesissupporting
confidence: 77%
“…Given these ratios, simulations demonstrate that the periclinal stress patterns (i.e., parallel to the tissue surface) in the outer walls of multilayered SAM models resemble those produced by shell models, thus validating earlier approaches ( Ali et al, 2019 ). A second important conclusion from this work is that maximal stress patterns in the anticlinal walls (i.e., perpendicular to the tissue surface) of both the epidermis and underlying cell layers are predominantly oriented anticlinally ( Ali et al, 2019 ), again matching observed microtubule and cellulose orientations ( Sakaguchi et al, 1988 ; Figure 1B ). This a priori indicates that loosening the walls of subepidermal cells or randomizing cellulose orientations may result in anticlinal cellular growth, which would account for the initial outward bulge associated with lateral organ formation (see further discussion on auxin’s influence on microtubules see below).…”
Section: A Mechanical Stress Cellulose Fibril Feedback Loop Patterns Plant Morphogenesissupporting
confidence: 77%
See 1 more Smart Citation
“…2011; Hervieux et al, 2017;Fox et al, 2018;Ali et al, 2019). Abstraction of cellular-scale FEM to a continuous sheet of material with defined cell scale information is also used to discretize tissuelevel details for simulation purposes (Bozorg et al, 2014;Hervieux et al, 2017;Kennaway and Coen, 2019).…”
Section: Box 3 Finite Element Modelsmentioning
confidence: 99%
“…However, at the cellular scale, plant mechanobiology is affected by physical connections to neighboring cells. Wall-to-wall adhesion adds external forces and responses that complicate mechanical characterization of any one cell 5,6 . Here, we employ pollen grains as a neighbor-less model system for biomechanical characterization of plant cells.…”
Section: Introductionmentioning
confidence: 99%